The Goldilocks challenge : right-fit evidence for the social sector - Gugerty, Mary Kay; Karlan, Dean S. (New York, NY : Oxford University Press, 2018)
"The recent push for impact measurement has been positive, but it has also led to wasted resources and often misleading data about what works. In The Goldilocks Challenge, Gugerty and Karlan put forth four key principles to guide organizations of all sizes to create strong, "right-fit" data collection systems" --
The CART principles : from too much and too little, to just right -- The theory of change --The CART principles -- Monitoring with the CART principles-- The CART principles for impact evaluation -- Collecting high-quality data -- Educate! --Developing a theory of change for "changemakers" -- BRAC : credible activity monitoring for action -- Salama SHIELD Foundation : the challenge of actionability -- - Invisible children uganda : an evolving monitoring and evaluation system -- Deworm the world : from impact evidence to implementation at scale -- Un Kilo de Ayuda: finding the right fit in monitoring and evaluation -- The institutional donor perspective -- The retail donor perspective -- Concluding thoughts and (hopefully) helpful resources.
Includes bibliographical references.
BIGD
Amazon
Keywords: Nonprofit organizations -- Evaluation; Organizational effectiveness -- Evaluation -- Methodology